Evaluating new treatments for anaplastic thyroid cancer. Issue 11 (2nd November 2022) - Coca-Pelaz, Andrés; Rodrigo, Juan P.; Lopez, Fernando; Shah, Jatin P.; Silver, Carl E.; Al Ghuzlan, Abir; Menke-van der Houven van Oordt, C.Willemien; Smallridge, Robert C.; Shaha, Ashok R.; Angelos, Peter; Mendenhall, William M.; Piazza, Cesare; et al.
ABSTRACT: Introduction: Anaplastic thyroid cancer (ATC) is one of the most lethal diseases known to humans with a median survival of 5 months. The American Thyroid Association (ATA) recently published guidelines for the treatment of this dreadful thyroid malignancy. Areas covered: This review presents the current therapeutic landscape of this challenging disease. We also present the results from trials published over the last five years and summarize currently active clinical trials. Expert opinion: Recent attempts to improve the prognosis of these tumors are moving toward personalized medicine, basing the treatment decision on the specific genetic profile of the individual tumor. The positive results of dabrafenib and trametinib for ATC harboring the BRAF V600E mutation have provided a useful treatment option. For the other genetic profiles, different drugs are available and can be used to individualize the treatment, likely using drug combinations. Combinations of drugs act on different molecular pathways and achieve inhibition at separate areas. With new targeted therapies, average survival has improved considerably and death from local disease progression or airway compromise is less likely with improvement in quality of life. Unfortunately, the results remain poor in terms of survival.